2000
DOI: 10.1136/pgmj.76.902.760
|View full text |Cite
|
Sign up to set email alerts
|

Whipple's disease

Abstract: Whipple's disease is a systemic bacterial infection and the common though not invariable manifestations are diarrhoea, weight loss, abdominal pain, and arthralgia. Arthritis or arthralgia may be the only presenting symptom, predating other manifestations by years. Virtually all organs in the body may be aVected, with protean clinical manifestations. Various immunological abnormalities, some of which may be epiphenomena, are described. The causative organism is Tropheryma whippelii.The disease is uncommon thoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
50
0
7

Year Published

2002
2002
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 28 publications
(36 reference statements)
0
50
0
7
Order By: Relevance
“…These pathognomonic PAS-positive macrophages may also be present in the peripheral and mesenteric lymph nodes and various other organs. 10 There were no arthralgia and abdominal pain in our patient. Our jejunal biopsies were also excluded from the Whipple's disease because of the absence of these foamy macrophages.…”
Section: Discussionmentioning
confidence: 84%
“…These pathognomonic PAS-positive macrophages may also be present in the peripheral and mesenteric lymph nodes and various other organs. 10 There were no arthralgia and abdominal pain in our patient. Our jejunal biopsies were also excluded from the Whipple's disease because of the absence of these foamy macrophages.…”
Section: Discussionmentioning
confidence: 84%
“…Whipple described a 36 year old medical missionary with weight loss, abdominal pain, polyarthritis, lymphadenopathy and fatty diarrhoea. In 1961, Paulley et al identified 'bacillary bodies' suggestive of an infectious agent [4]. In 1992, polymerase chain reaction was used to identify the micro-organism and it was named Tropheryma whippelii (Greek, trophe: nourishment; eryma: barrier, due to the resulting malabsorption) [5].…”
Section: Discussionmentioning
confidence: 99%
“…Los macrófagos PAS + disminuyen lentamente y pueden observarse en la biopsia intestinal hasta un año después de haber instaurado un tratamiento antibiótico correcto (1,2,15). Por lo tanto su presencia no deber usarse como indicador de la eficacia del mismo.…”
Section: Fig 2 Tc Abdominal: Múltiples Adenopatías Retroperitonealeunclassified